Madame ambassador : behind the scenes with a candid Israeli diplomat - Herzl, Tova (Rowman and Littlefield, 2015)
'Madame Ambassador' is an intimate description of what being an ambassador is really like. Tova Herzl draws on her twenty-one year career and shares her unique experiences as a single, Jewish orthodox woman serving as Israel's Ambassador to paint a vivid, entertaining picture of the lives and work of contemporary diplomats.